Business modeling in process-oriented organizations for RUP-based software development - Duarte, Francisco J. (2006)
Several organizations are nowadays not particularly comfortable with their internal structuring based on a hierarchical arrangement (sub-divided in departments), where collaborators with a limited view of the overall organization perform their activities. Those organizations recognize the need to move to a model where multi-skilled teams run horizontal business processes that cross the organization, and impact suppliers and clients. To develop software systems for any organization, the development process must always be appropriate and controlled. Additionally for organizations who want to migrate to a horizontal business processes view, it is required to model the organizational platform where the organizational processes will run. This necessity is also true when the organization under consideration is a software house. In this chapter, a proposal of a generic framework for process-oriented software houses is presented. The way of managing the process model and the instantiation of their processes with the Rational Unified Process (RUP) disciplines, whenever they are available, or with other kind of processes is recommended as a way to control and define the software development process. To illustrate the usefulness of the proposal, it is presented how the generic reference framework was executed in a real project called “Premium Wage” and shown, in some detail, the created artifacts (which include several UML models) during the development phases following the RUP disciplines, especially the artifacts produced for business modeling.